2011
DOI: 10.1590/s1806-66902011000400001
|View full text |Cite
|
Sign up to set email alerts
|

Cokrigagem na estimativa dos teores de Ca e Mg em um Latossolo Vermelho distroférrico

Abstract: Latossolo Vermelho Distroférrico, amostrou-se a camada de 0-0,2 m, utilizando grade de 25 x 25 m, totalizando 60 pontos em 5,02 ha. Realizou-se, inicialmente, análise descritiva e de correlação e, posteriormente, análise geoestatística, para identificar a dependência espacial das variáveis estudadas. Utilizando a técnica da cokrigagem, os valores de pH mostraram-se eficientes na estimativa de teores de Ca e Mg, devido a elevada correlação entre esta co-variável e as variáveis a serem estimadas.Palavras-chave -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
2
1
0
5
Order By: Relevance
“…Similar results were obtained by Bottega et al (2011), who estimated the levels of Ca 2+ and Mg 2+ as a function of pH using cokriging in a Red Latosol. The authors found a strong spatial dependence between pH and Ca (DSD = 16.1%) and between pH and Mg (DSD = 15.8%), indicating the possibility of using pH to estimate Ca 2+ and Mg 2+ in unsampled sites in the study area, reducing the costs of sampling and laboratory measurements.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were obtained by Bottega et al (2011), who estimated the levels of Ca 2+ and Mg 2+ as a function of pH using cokriging in a Red Latosol. The authors found a strong spatial dependence between pH and Ca (DSD = 16.1%) and between pH and Mg (DSD = 15.8%), indicating the possibility of using pH to estimate Ca 2+ and Mg 2+ in unsampled sites in the study area, reducing the costs of sampling and laboratory measurements.…”
Section: Discussionsupporting
confidence: 84%
“…The cross-variograms showed intermediate range values, however in all analyzed situations the values were higher than those of the main variable, in the case of foliar P. This behavior was most evident for the species conilon, where the range increased by 61 m. These results corroborate those found by Bottega et al (2011) and Silva et al (2010), who claimed that the cross-variogram range values tend to rise in circumstances where the spatial continuity of the auxiliary variable is greater than the main variable. Table 4 shows the distribution classes of foliar P contents and the concentration of P-rem in the soils under study.…”
Section: Resultssupporting
confidence: 88%
“…Pode-se, também, efetuar a interpolação por co-krigagem, a partir de estimativas de duas variáveis que se correlacionam (primária e secundária). Os dois processos podem ser descritos como métodos que minimizam a variância estimada por meio de análise de regressão, levando-se em conta a dependência entre os dados distribuídos no espaço (Trangmar et al, 1985;Bottega et al, 2011). Na tentativa de se estabelecer um indicador da qualidade química do solo, que venha a elucidar as possíveis causas de degradação das pastagens de Brachiaria decumbens, para o local estudado, a partir dos atributos da planta e do solo, este trabalho objetivou: a) analisar a variabilidade desses atributos e b) definir as correlações lineares e espaciais entre os atributos da planta e do solo.…”
Section: Introductionunclassified